The Urgency of Regulating the Rescission of Child Adoption: A Comparative Study on Upholding the Best Interests of the Child - Farradhisya Ririz Nabila; Akhmad Budi Cahyono (Universitas Lampung, 2025)
The absence of specific regulations governing the cancellation of child adoption in Indonesia has created a legal vacuum that undermines the principle of the best interests of the child. This study aims to develop an ideal legal framework for adoption cancellation to prevent practices contrary to child protection principles. Using a doctrinal approach and a comparative analysis with the Philippine legal system, the research emphasizes the urgency of establishing clear regulations that prioritize the child’s welfare in every judicial decision. The proposed reform integrates Law No. 23 of 2004 on the Elimination of Domestic Violence (UUPKDRT) and Government Regulation No. 54 of 2007 on the Implementation of Child Adoption to provide a comprehensive legal basis. Strengthening these instruments would ensure that violence by adoptive parents constitutes valid grounds for cancellation while safeguarding the child’s rights to continuous care, protection, and development before and after annulment.